The Role of Baznas in Program Implementation for MSMEs: Case Study at Baznas Microfinance in Sawojajar Village, Malang - Icha Puspita; Rahmad Hakim; Sri Cahyaning Umi Salama (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
This study aims to determine how the role of BAZNAS in the implementation of the program for MSMEs: A Case Study on BAZNAS Microfinance in Sawojajar Village, Malang. Baznas Microfinance in Sawojajar Village itself has helped mustahik in developing their business and is also free from moneylenders with business capital problems which are obstacles for micro business actors. This research uses descriptive qualitative research. Data collection techniques used are data collection in the form of interviews, and documentation. Data analysis in this research is using data collection, data condensation, data presentation and verification/conclusion. The results of this study indicate that with this program being able to maintain their business during the pandemic, there are even some MSMEs that experienced an increase in turnover during the pandemic after being assisted by BAZNAS. So, by showing a progress, growth, evolution and an increase from what has been planned. In implementing its program, BAZNAS Microfinance in Sawojajar Village has implemented it for mustahik by helping those affected by this pandemic to develop their business and increase sales turnover so that it is helped in the family economy